2014
DOI: 10.1186/s40510-014-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Social impairment of individuals suffering from different types of chronic orofacial pain

Abstract: BackgroundThe daily life of patients suffering from orofacial pain is considerably impaired as compared to healthy subjects. The aim of this study was to investigate the influence of different categories of orofacial pain on the habitual life of adult individuals.MethodsSeven hundred eighty-one individuals with orofacial pain were recruited from an initial sample of 1,058 patients. All the individuals were allocated to groups according to their diagnosis: myofascial pain (group A, 676 subjects, 525 females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…In addition, the presence of primary headache together with TMD negatively influences the management of TMD 21 . The association between severe depression and non-specific physical symptoms and group II observed in this study is in line with an Italian study which has shown that when there is muscle TMD and migraine, there is major impairment of the psychological status of individuals, determining high levels of somatization 22 . By identifying modifiable behavioral factors, such as stress or diet handling, in addition to the evaluation of genetic, environmental, social and cultural factors involved in the relationship between TMD and migraine, this might be prevented with management strategies for both conditions 5 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the presence of primary headache together with TMD negatively influences the management of TMD 21 . The association between severe depression and non-specific physical symptoms and group II observed in this study is in line with an Italian study which has shown that when there is muscle TMD and migraine, there is major impairment of the psychological status of individuals, determining high levels of somatization 22 . By identifying modifiable behavioral factors, such as stress or diet handling, in addition to the evaluation of genetic, environmental, social and cultural factors involved in the relationship between TMD and migraine, this might be prevented with management strategies for both conditions 5 .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding large sample studies (N ≥ 300) in TMD seeking treatment (ie institutional or clinical) patients which have also used the RDC/TMD Axis I or II within the last 10 years, we have found interesting results. The sample among the reviewed studies has ranged from 308 to 3263 TMD patients, the mean age has varied from 19 to 44 years, and the proportion of women has varied from 57.3%‐88% . This yields odds ranging approximately from 3:1 to 9:1, which is substantially larger than what we have found among non‐TMD population‐based sample in this study, that is, odds of 2:1.…”
Section: Discussionmentioning
confidence: 58%
“…Most studies report that about a quarter of the population had orofacial pain at least once during the previous 6 months (2-4,7). The prevalence and characteristics of pain are determined by demographic, economic, and psychosocial factors (e.g., current stress level, sensitivity, mood, fear, and psychophysical and mental states) (15).…”
Section: Discussionmentioning
confidence: 99%